Molecular Docking Analysis of Phytocompounds from Hyptis Verticillata as Potential Inhibitors of Human Cyclooxygenase-2 (COX-2) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Cyclooxygenase-2 (COX-2) is a key inducible enzyme in the inflammatory pathway, catalyzing the conversion of arachidonic acid into prostaglandins that mediate pain, fever, and inflammation. Selective COX-2 inhibitors such as celecoxib and rofecoxib have demonstrated strong therapeutic effects but are associated with adverse cardiovascular and gastrointestinal complications, underscoring the need for safer alternatives. Medicinal plants represent a valuable source of novel bioactive compounds with promising anti-inflammatory properties. Hyptis verticillata, a member of the Lamiaceae family, has been widely used in ethnomedicine for treating fever, colds, and inflammatory conditions, and is known to contain diverse phytochemicals including terpenoids, flavonoids, sterols, and essential oils. This study aimed to evaluate the molecular docking interactions of phytocompounds from H. verticillata with human COX-2 (PDB ID: 6COX) as potential natural anti-inflammatory agents. Seven phytochemicals reported in previous phytochemical profiling of the plant were docked against the COX-2 active site using AutoDock Vina implemented in PyRx, and their interactions compared with reference inhibitors celecoxib and rofecoxib. Binding affinities ranged from −3.7 to −8.2 kcal/mol. Squalene demonstrated the strongest affinity (−8.2 kcal/mol), comparable to rofecoxib (−8.2 kcal/mol), while aliphatic hydrocarbons such as 1-octadecyne (−6.9 kcal/mol) and 1-fluorodecane (−6.1 kcal/mol) showed moderate activity. Celecoxib, unexpectedly scoring −3.7 kcal/mol, highlighted potential docking protocol limitations that warrant revalidation. Interaction analysis revealed that hydrophobic contacts dominated ligand binding, consistent with the structural hydrophobicity of the COX-2 catalytic tunnel. Although squalene showed high docking affinity, ADMET predictions indicated poor solubility and oral bioavailability, limiting its drug-likeness. In contrast, smaller hydrocarbons displayed more favorable pharmacokinetic profiles but weaker binding energies. These findings suggest that H. verticillata harbors compounds with structural potential for COX-2 inhibition, though optimization and experimental validation are required. The study provides a computational foundation for developing safer plant-derived anti-inflammatory agents.